Utilizing Solubility Differences to Achieve Regiocontrol in the Synthesis of Substituted Quinoline-4-carboxylic Acids - Lindsay-Scott, Peter J.; Barlow, Helen (Synlett, 2016)
A practical method for the regiocontrolled synthesis of substituted quinoline-4-carboxylic acids is described. Solubility differences between the product quinoline regioisomers enable their facile separation, thus avoiding any challenging chromatographic purifications and allowing access to highly substituted quinoline compounds in three steps from commercially available anilines.
Keywords: heterocycles; quinolones; isatins; regioisomers; cyclization